2018
DOI: 10.1016/j.jalz.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Transitions across cognitive states and death among older adults in relation to education: A multistate survival model using data from six longitudinal studies

Abstract: This study highlights the importance of education in later life and that early life experiences can delay later compromised cognitive health. This study also demonstrates the feasibility and benefit in conducting coordinated analysis across multiple studies to validate findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 56 publications
3
62
0
Order By: Relevance
“…Multistate models facilitate a better understanding of transitions between health states and death among the oldest old. Recent developments in multistate modeling make it possible to study the role of risk factors, such as sex, in transitions between these states [11]. Moreover, based on multistate models, overall, healthy, and unhealthy life expectancies (LEs) may be estimated for specific groups [12].…”
Section: Introductionmentioning
confidence: 99%
“…Multistate models facilitate a better understanding of transitions between health states and death among the oldest old. Recent developments in multistate modeling make it possible to study the role of risk factors, such as sex, in transitions between these states [11]. Moreover, based on multistate models, overall, healthy, and unhealthy life expectancies (LEs) may be estimated for specific groups [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to the theory, individuals with high CR remain clinically normal in the early stage of AD, but the rate of decline in cognitive performance is more rapid than in those with low CR in the late stage of AD [34]. Indeed, there is a considerable amount of evidence supports that higher levels of CR protect against progression of from SCD to MCI [35,36], and diagnostic conversion for normal cognition [37,38]. In this sense, our ndings from this study are consistent with the theory of CR.…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that low educational attainment has the highest population-attributable risk (PAR) of AD worldwide (19.1%, 95% CI 12.3-25.6) [7]. Conversely, higher level of education has been shown to prevent or delay the onset of dementia [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Factors contributing to the construction of an adequate cognitive reserve will help delay the arrival of senile dementia, while, a lack of these factors constitutes increasing risks. In addition to genetic factors [6], a growing number of modifiable factors have been related to senile dementia, such as occupational complexity [7][8][9], educational attainment [10][11][12], marital status [13], socioeconomic status [14], and social networks [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Just recently, a data analysis report integrating six longitudinal studies demonstrated that older individuals with high educational attainment and high socioeconomic status have remarkably longer non-cognitively impaired life expectancies as opposed to those with low educational attainment and low socioeconomic status [19]. This observation suggests that education and socioeconomic status are synergistic resilience factors against the onset of senile dementia.…”
Section: Introductionmentioning
confidence: 99%